Niger : Staff Report for the 2000 Article IV Consultation and Request for a Three-Year Arrangement under the Poverty Reduction and Growth Facility. (IMF Staff Country Reports; Country Report, 2001)
Niger has experienced a significant program interruption. Executive Directors supported the efforts to resume the economic and structural reform program interrupted, and restore budgetary transparency, improve governance, and accelerate structural reforms. They welcomed the efforts to resume financial relations with development partners, maintain social and political stability, and stressed the need for fiscal consolidation and monitoring of banks' compliance with prudential regulations. They urged the authorities to continue efforts to improve quality and timeliness, inclusive of social data.